Nuclear receptors and their role in epstein — barr virus induced b cell transformation - Yenamandra, S.P.; Klein, G.; Kashuba, E. (Experimental Oncology, 2009)
Epstein — Barr virus (EBV) is a lymphotropic virus that infects more than 90% of the human population, and targets B cells for infection. Infection of human B cells leads to the malignant transformation and eventual immortalization. In latency III infection six EBV-encoded nuclear antigens (EBNAs) and three latent membrane proteins (LMPs) are expressed in the transformed cells that can grow as a lymphoblastoid cell lines in vitro. These proteins hijack the normal B cell growth pathways by activating the constitutive growth promotion and external survival signals. We have determined a set of the nuclear receptors that are up- (and down-) regulated in the latency III infected cells at the mRNA level. In the present paper we discussed the possible role of these receptors in B cell transformation upon EBV infection based on the literature data.